Physiochemical Characterization of Ethiopian Mined Kaolin Clay through Beneficiation Process - Adane Adugna Ayalew (Advances in Materials Science and Engineering)
Kaolin mineral is a commercially solid powder with a comparatively low level of purity and is regularly used for a variety of applications, including filler, paints, ceramics, adsorbents, and paper. In Ethiopia, the kaolin clay mineral is significant for financial growth as the raw material used in the industry sector. However, slight consideration was given to the chemical, physical, mineralogical, and morphological properties of kaolin. In this study, the property of kaolin is investigated by using advanced instruments such as X-ray diffraction (XRD), X-ray fluorescence analysis (XRF), Fourier-transform infrared spectroscopy (FTIR), thermogravimetric analysis (TGA), and differential thermogravimetric analysis (DTA). Based on the XRF test, the main component of kaolin clay contains SiO2 (58.73%), Al2O3 (24.35%), K2O (5.36%), and other impurities, including Fe2O3 (2.06%) and TiO2 (0.13%). The FTIR spectra displayed the functional groups Si-O, Al-OH, Al-O, and Si-O-Al. The XRD diffractogram identified kaolin clay as the main mineral phase in the existence of quartz, halloysite, and chlorite.